Day-case total hip arthroplasty: a literature review and development of a hospital pathway - Thompson, Joshua W. (Bone Jt Open, 2021)
AIMS: We present the development of a day-case total hip arthroplasty (THA) pathway in a UK National Health Service institution in conjunction with an extensive evidence-based summary of the interventions used to achieve successful day-case THA to which the protocol is founded upon. METHODS: We performed a prospective audit of day-case THA in our institution as we reinitiate our full capacity elective services. In parallel, we performed a review of the literature reporting complication or readmission rates at ≥ 30-day postoperative following day-case THA. Electronic searches were performed using four databases from the date of inception to November 2020. Relevant studies were identified, data extracted, and qualitative synthesis performed. RESULTS: Our evaluation and critique of the evidence-based literature identifies day-case THA to be safe, effective, and economical, benefiting both patients and healthcare systems alike. We further validate this with our institutional elective day surgery arthroplasty pathway (EDSAP) and report a small cohort of successful day-case THA cases as an example in the early stages of this practice in our unit. CONCLUSION: Careful patient selection and education, adequate perioperative considerations, including multimodal analgesia, surgical technique and blood loss management protocols and appropriate postoperative pathways comprising reliable discharge criteria are essential for successful day-case THA. Cite this article: Bone Jt Open 2021;2(2):93–102.